Gender Representation and Traditional Character Roles in the Television Series Nightmares and Daydreams - Kennedy Purnama Chandra; Viriena Puspita; Kevin Irianto; Satriyadi Mandala Putra (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The purpose of this study is to examine the depiction of gender and the traditional role of characters in the television series Nightmares and Daydreams. The television series Nightmares and Daydreams was made to provide an explanation to the public regarding the dynamics of family life problems in Indonesia combined with science fiction works. This study uses a narrative analysis approach with Walter Fisher's narrative paradigm. The series featured in each episode of Nightmares and Daydreams shows that it has narrative possibilities in the context of everyday life. The traditional role of the figure reflects the cultural life of Indonesia, which has a tradition of talking while at home. Returning to the role of gender, which has an important role in depicting problems that are often experienced in life in Indonesia, by combining science fiction works. The findings show that the series challenges gender stereotypes through several main characters in each episode who are often placed in conflict between traditional values and personal identity. By using qualitative methods, this research explores how men and women are portrayed through social roles, emotional expression, and life dynamics in stories. This research also highlights how popular media can play an important role in shaping gender meaning in society.